Mechanisms and Future of Non-Small Cell Lung Cancer Metastasis - Zhu, Tianhao; Bao, Xunxia; Chen, Mingyu; Lin, Rui; Zhuyan, Jianan; Zhen, Timing; Xing, Kaichen; Zhou, Wei; Zhu, Sibo (Frontiers in Oncology, 2020)
Lung cancer, renowned for its fast progression and metastatic potency, is rising to become a leading cause of death globally. It has been long observed that lung cancer is particularly ept in spawning distant metastasis at its early stages, and it can readily colonize virtually any human organ. In recent years, cancer research have shed light on why lung cancer is endowed with its exceptional ability to metastasize. In this review, we will take a comprehensive look at the current research on lung cancer metastasis, including molecular pathways, anatomical features and genetic traits that make lung cancer intrinsically metastatic, as we go from lung cancer’s general metastatic potential to the particular metastasis mechanisms in multiple organs. We highly concerned about the advanced discovery and development of lung cancer metastasis, indicating the importance of lung cancer specific gene mutations, heterogeneity or biomarker discovery, and discussing potential opportunities and challenges. We will also introduce some current treatments that targets certain metastatic strategies of non-small cell lung cancer(NSCLC). Advances made in these regards could be critical to our current knowledge base of lung cancer metastasis.